Regional Economic Outlook, November 2006, Western Hemisphere. (Regional Economic Outlook, 2006)
This Western Hemisphere Regional Economic Outlook covers the United States, Canada, Latin America, and the Caribbean. The report reviews recent economic developments, discusses the economic outlook, and outlines risks and challenges ahead.